2019
DOI: 10.1021/acsami.9b07520
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Electronic Textiles Using Silver Nanowire Composites

Abstract: Textiles represent an appealing platform for continuous wearable applications due to the exceptional combination of compliance, water vapor permeability, and comfortableness for long-term wear. We present mechanically and electrically robust integration of nanocomposites with textiles by laser scribing and heat press lamination. The simple and scalable integration technique enables multifunctional E-textiles without compromising the stretchability, wearability, and washability of textiles. The textile-integrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
104
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(104 citation statements)
references
References 64 publications
0
104
0
Order By: Relevance
“…Recently, by combining traditional textile technology with electrical engineering, e-textile has become an attractive candidate for wearable sensors ( Afroj et al., 2019 ; Hu et al., 2019 ; La et al., 2018 ; Wang et al., 2021 ; Zhao et al., 2019b ). Specifically, fiber strain sensors, known as the convergence of strain sensing materials (conductive materials) and textile platforms, have been used to monitor various human activities ( Gupta et al., 2018 ; Li et al., 2017 ; Liao et al., 2019 ; Yao et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, by combining traditional textile technology with electrical engineering, e-textile has become an attractive candidate for wearable sensors ( Afroj et al., 2019 ; Hu et al., 2019 ; La et al., 2018 ; Wang et al., 2021 ; Zhao et al., 2019b ). Specifically, fiber strain sensors, known as the convergence of strain sensing materials (conductive materials) and textile platforms, have been used to monitor various human activities ( Gupta et al., 2018 ; Li et al., 2017 ; Liao et al., 2019 ; Yao et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Textile electrodes received considerable attention because they can be easily integrated into garments to enable long-term monitoring. Textile electrodes are usually fabricated using standard fabric manufacturing techniques such as knitting, weaving, embroidery of conductive fibers, or they are manufactured by applying conductive materials onto finished textiles with various techniques like electroplating, physical vapor deposition, chemical polymerization, coating and printing methods [13], silver nanowires (AgNWs) and polydimethylsiloxane (PDMS)-based electrodes [14]. While research mainly focused on the development of textile electrode for ECG [11], the possibility to continuously assess muscle activity through electromyography (sEMG) is of high interest.…”
Section: Introductionmentioning
confidence: 99%
“…Percolation networks comprising conductive materials (CMs) have been the most widely employed candidates as stretchable heating resistors primarily due to their inherent stretchability and relatively simple preparation. [6][7][8][9][10][11][12][13][14] The CMs that are usually utilized include carbon nanotubes (CNTs), 6 silver nanowires (AgNWs) [7][8][9] and nanobers, 10 AgNW/CNT 11,12 and conductive polymer/reduced graphene oxide composites, 13 and superaligned CNT sheets. 14 The conductive percolation networks can be easily integrated with elastomer and fabric substrates either by directly coating the CMs 6,7,[10][11][12][13] or by transferring pristine or patterned CM networks onto stretchable substrates.…”
Section: Introductionmentioning
confidence: 99%
“…14 The conductive percolation networks can be easily integrated with elastomer and fabric substrates either by directly coating the CMs 6,7,[10][11][12][13] or by transferring pristine or patterned CM networks onto stretchable substrates. 8,9,14 However, random morphologies of CM networks generally hinder the reproducibility and uniformity of the devices in terms of both fabrication and performance. Moreover, it has been reported that the electrothermal performance of these types of heaters degrade with increasing strain, predominantly due to the gradual loss of electrical pathways in their CM networks.…”
Section: Introductionmentioning
confidence: 99%